2022
DOI: 10.1007/s11695-022-06017-9
|View full text |Cite
|
Sign up to set email alerts
|

The Genus Parabacteroides Is a Potential Contributor to the Beneficial Effects of Truncal Vagotomy–Related Bariatric Surgery

Abstract: Purpose Evidences about the gut microbiota role in weight loss after bariatric surgery (BS) are growing. The objective of this study was to observe the changes of gut microbiota after sleeve gastrectomy (SG) and SG plus truncal vagotomy (SG-TV) and identify specific microbes that may contribute to the improvement of obesity after surgeries. Materials and Methods Forty high-fat diet-induced obesity (DIO) mice were randomized to SG, SG-TV, or sham operation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Particularly, the genus Vampirovibrio, which exhibited an upsurge in both egg-fed and egg FMT rodents, has been previously associated with metabolic enhancements across diverse studies. For instance, this genus was found to be heightened in the intestines of obese mice subjected to bariatric surgery and showcased an inverse correlation with body weight and fasting glycemic levels (Liang et al, 2022). Taking into account the findings of the present investigation alongside prior research, it can be surmised that the genus Vampirovibrio might harbor protective attributes against obesity.…”
Section: Discussionsupporting
confidence: 54%
“…Particularly, the genus Vampirovibrio, which exhibited an upsurge in both egg-fed and egg FMT rodents, has been previously associated with metabolic enhancements across diverse studies. For instance, this genus was found to be heightened in the intestines of obese mice subjected to bariatric surgery and showcased an inverse correlation with body weight and fasting glycemic levels (Liang et al, 2022). Taking into account the findings of the present investigation alongside prior research, it can be surmised that the genus Vampirovibrio might harbor protective attributes against obesity.…”
Section: Discussionsupporting
confidence: 54%
“…This is not the first time that the Parabacteroides genus has been linked to body weight. The majority of studies denote a higher Firmicutes:Bacteroidetes ratio and a generalized reduction in species variation in individuals with increased body weight or obesity [ 34 ], and different studies have found positive associations between genus and normal weight or weight loss in mice, as well as fat loss in humans [ 35 , 36 , 37 , 38 , 39 ]. It is plausible that the corresponding SNPs are further linked to BMI through the genus’s role in gut production of bile acids and succinate, which have, in turn, been associated with reduction in body weight [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the vagus nerve is crucial in these mechanisms, certain microbiota-driven effects on weight loss post-bariatric surgery occur independently of the vagus nerve's participation. In particular, the genus Parabacteroides has been correlated with positive effects in post-surgical mice [66]. In a recent study, mice undergoing SG with truncal vagotomy had increased Eubacterium, Prevotella, and Parabacteroides that were correlated with enhanced weight loss, though Parabacteroides was exclusive to the subgroup that underwent SG with truncal vagotomy, which experienced greater weight loss compared to both the sham group and the group that had only SG [66].…”
Section: Bariatric Surgery Gut Microbiota Cytokines and Inflammationmentioning
confidence: 99%
“…In particular, the genus Parabacteroides has been correlated with positive effects in post-surgical mice [66]. In a recent study, mice undergoing SG with truncal vagotomy had increased Eubacterium, Prevotella, and Parabacteroides that were correlated with enhanced weight loss, though Parabacteroides was exclusive to the subgroup that underwent SG with truncal vagotomy, which experienced greater weight loss compared to both the sham group and the group that had only SG [66]. Parabacteroides is known for its anti-obesity effects, although these benefits are primarily immunomodulatory and occur through the enhancement of the gut barrier [67].…”
Section: Bariatric Surgery Gut Microbiota Cytokines and Inflammationmentioning
confidence: 99%